EU HUMANITARIAN ACTIVITIES IN THE CENTRAL ASIAN COUNTRIES OF THE POST-SOVIET SPACE: CHALLENGES AND OPPORTUNITIES FOR RUSSIA - Leili Rustamovna Rustamova (Vestnik RUDN. International Relations, 2018)
In connection with the growing security threats related to migration flows from the troubled regions of the world and the need to diversify transport flows of hydrocarbon resources, the EU began to pay attention to the cooperation with the Central Asian countries. Within the framework of the EU Strategy for Central Asia, several priority areas were adopted, according to which it was planned to build relations with the post-Soviet republics most closely. This study aims to analyze the main projects in the field of humanitarian cooperation between the EU and the Central Asian countries and to establish to what extent such projects are competitive in comparison with the Russian ones, as the countries of the region belong to the area of Russian interests. To achieve this goal the author used general scientific methods and systematic approach. While analyzing the documents which give the theoretical explanation of the importance of the region for European partners and materials of foreign and Russian researchers devoted to the humanitarian problems of the region and the main results of the EU Strategy for Central Asia, the author comes to the conclusion that the projects of humanitarian cooperation of the EU with the countries of Central Asia do not take into account the national characteristics and priority needs of the former Soviet republics. However, many projects are quite competitive in comparison with the Russian ones and in order to stay as a strategic partner in the long-term future for the countries of the region Russia needs to take into account their best characteristics and achievements.